Human, Technologies and Quality of Education, 2021 2021
DOI: 10.22364/htqe.2021.09
|View full text |Cite
|
Sign up to set email alerts
|

Ability to Deal with it: Self-Management and Problem-Solving Skills, Motivation and Routines Helped High-School Students During the COVID-19 Pandemic

Abstract: As the COVID-19 pandemic unfolded, more than 1.5 billion students worldwide started learning remotely, and they faced a range of challenges: a lack of immediate support from teachers, problems with technology, psychological well-being and difficulties in independently coping with their duties. The aim of this study was to understand what helped students cope with distance learning and what hindered and made it difficult for students, as well to examine students’ self-assessed problem-solving and self-managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 18 publications
0
15
1
Order By: Relevance
“…The pandemic period and the distance learning have raised questions globally about which skills, abilities and other factors (e.g., external factors such as support from parents or teachers) are crucial for students to maintain their academic performance and well-being as much as possible during this time ( Rosen et al 2021 ; Hacatrjana 2021a ), and some recent data have indicated a decrease in students’ academic performance that is probably due to the pandemic ( Engzell et al 2021 ). In this study, the focus is particularly on the individual aspects related to the students’ own skills and abilities to deal with the new situation.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The pandemic period and the distance learning have raised questions globally about which skills, abilities and other factors (e.g., external factors such as support from parents or teachers) are crucial for students to maintain their academic performance and well-being as much as possible during this time ( Rosen et al 2021 ; Hacatrjana 2021a ), and some recent data have indicated a decrease in students’ academic performance that is probably due to the pandemic ( Engzell et al 2021 ). In this study, the focus is particularly on the individual aspects related to the students’ own skills and abilities to deal with the new situation.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the focus is particularly on the individual aspects related to the students’ own skills and abilities to deal with the new situation. Students (most studies were performed in primary schools or in high schools) have reported in questionnaires that their ability to plan their time has helped them during distance learning, while also indicating feeling stress regarding the management of assignments on time and having insufficient planning skills, self-organization and management skills, which caused difficulties with remote learning ( Scott et al 2021 ; Ministry of Education and Science of Latvia 2020 ; Rogers et al 2021 ; Hacatrjana 2021a ). This means that during the pandemic and distance learning many students were aware that they lacked some skills to learn effectively.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations